Correlation between Surface Texture, Wettability and Mechanical Strength of Polylactic Acid Parts Fabricated by Fused Filament Fabrication. - Bañón-García, Fermín; Bermudo-Gamboa, Carolina; López-Fernández, José Andrés; Trujillo-Vilches, Francisco Javier; Martín-Béjar, Sergio (MDPI, 2024)
This research investigates the generation and evaluation of various geometric surface textures on PLA components produced via fused filament fabrication (FFF). Textures, including grooves, pyramids, and cylinders, were created at different depth levels on the PLA surfaces. The surface quality of these textures was assessed using a 3D optical system, focusing on area parameters such as Sa and Sz. The wettability of each texture was evaluated through contact angle and sliding angle tests, revealing the ability to modulate contact angles and achieve either hydrophobic or hydrophilic surfaces depending on the texture type. Subsequently, pairs of textured PLA pieces were bonded using a cyanoacrylate adhesive following standardised protocols, and shear tests were conducted to determine the maximum shear stress at bond (τmax) of each texture. Notably, textured surfaces generally exhibited hydrophobic properties that reduce the adhesion between the adhesive and the piece, leading to reduced maximum shear stress at bond values compared to non-textured surfaces. However, groove textures notably increased τmax values. The results were analysed to establish correlations between surface quality, wettability, and shear strength. This comprehensive evaluation aims to elucidate the influence of surface texture on the mechanical performance and adhesive properties of FFF-manufactured PLA components.
Keywords: Procesos de fabricación; Polímeros; Superficies (Tecnología); Materiales - Textura; Wettability; FFF; PLA; Texture; shear strength; Surface quality; Wettability